2019
DOI: 10.1089/tmj.2018.0270
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Whistle and Smart Phone Application for Peak Flow Recordings in Asthmatic Children: A Feasibility Study

Abstract: Introduction: Variable airflow obstruction that can be confirmed by diurnal variability of peak expiratory flow (PEF) >13% is an important characteristic of asthma. Home monitoring of PEF may be helpful to diagnose and monitor asthma. In this feasibility study, we aimed to study if asthmatic children can measure PEF at home twice daily during a 4-week period using a device designed as a “whistle” and a smart phone software application.Materials and Methods: Twice daily during 4 weeks, children aged 5–12 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In theory, a video examination is possible (eg, using vision to assess a patient's skin color or guiding a relative to use a blood pressure monitor). Studies on, for example, chronic obstructive pulmonary disease [11] and asthma [12], show that patients can use technology to monitor their own condition.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, a video examination is possible (eg, using vision to assess a patient's skin color or guiding a relative to use a blood pressure monitor). Studies on, for example, chronic obstructive pulmonary disease [11] and asthma [12], show that patients can use technology to monitor their own condition.…”
Section: Introductionmentioning
confidence: 99%
“…Several home PFTs have been developed with the aim to enhance patients' self-management (41,47). Their use helps to overcome the infection control issues, as compared with laboratory tests.…”
Section: Home Pft Measurementsmentioning
confidence: 99%
“…Their use helps to overcome the infection control issues, as compared with laboratory tests. Most of these PFTs regard PEF and spirometry (13,(41)(42)(43)(44)(45)(46)(47)(51)(52)(53). Unsupervised measurements tend to be lower at home than in the laboratory, suggesting the need for patients' coaching (59,60).…”
Section: Home Pft Measurementsmentioning
confidence: 99%
“…Although forced spirometry is important in the early diagnosis of chronic obstructive pulmonary disease (COPD) and asthma, web-based remote support demonstrated better quality of testing in the primary-care setting using smartphone applications for peak flow recordings. 39 A systematic review of telehealth in cystic fibrosis patients showed significant findings related to increased use of antibiotics and improved spirometry stability. 40…”
Section: Respiratorymentioning
confidence: 99%
“…Using rating scales or severity scores as indicators of disease activity can provide objective measures. 39 Concurrently, patients may be asked to report symptoms over a period of time utilising web-based self-management programmes. 44…”
Section: Gastrointestinalmentioning
confidence: 99%